1981
DOI: 10.1042/bj2000449
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative importance of non-skeletal-muscle Nτ-methylhistidine and creatine in human urine

Abstract: The excretion of N tau-methylhistidine and creatinine was determined in a totally paralysed patient wih neither macroscopic nor microscopic detectable skeletal-muscle tissue. In this subject, it was possible for the first time to measure the basal non-skeletal-muscle-dependent excretion of N tau-methylhistidine and creatinine per 24 h and per kg of non-muscular body weight, 1.15 mumol (N tau-methylhistidine) and 35 mumol (creatinine) respectively. For the calculation of myofibrillar protein breakdown and skele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…The values for BUN, K, uric acid, Ca, Ca ++ , and Pi were significantly higher in pigs less than six months of age, a possible indication of poor kidney function (Figure 1). However, the level of Cr, an indicator of kidney function, was significantly lower in young pigs, possibly due to the low muscle volume [21]. Additionally, TIBC, UIBC and RDW were significantly higher in young pigs, but RBC, Hb, HCT, MCHC and MCV were significantly lower in young pigs (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The values for BUN, K, uric acid, Ca, Ca ++ , and Pi were significantly higher in pigs less than six months of age, a possible indication of poor kidney function (Figure 1). However, the level of Cr, an indicator of kidney function, was significantly lower in young pigs, possibly due to the low muscle volume [21]. Additionally, TIBC, UIBC and RDW were significantly higher in young pigs, but RBC, Hb, HCT, MCHC and MCV were significantly lower in young pigs (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the amount of myofibrillar proteins, the turnover rate determines the amount of 3MH that is produced. Since intestine is thought, in particular, to have a high turnover rate, it might contribute significantly to Wb 3MH production [37][38][39][40][41][42].…”
Section: Wb Versus Organ Levelmentioning
confidence: 99%
“…There is growing evidence that this is not so. For example, Afting and co-workers showed that there was considerable residual excretion of 3-methylhistidine and creatinine in a paralysed patient, who on later autopsy was declared to have no detectable skeletal muscle [37]. The 3-methylhistidine excretion could have accounted for between 20 and 80% of the range of excretion in normal subjects.…”
Section: Evidence From Studies In Manmentioning
confidence: 99%